ANALISIS PERUBAHAN TUTUPAN LAHAN DAN KONTRIBUSI HUTAN KEMASYARAKATAN DALAM PENYEDIAAN CADANGAN KARBON DI DAS JANGKOK - Markum Markum; K. Hairiah; D. Suprayogo; E. Ariesoesiloningsih (BUANA SAINS, 2012)
People who live around Jangkok Watershed in Lombok in general practices agroforestry system under Community Based Forest Management (CBFM) scheme. Objective of this reseach is to estimate changes of carbon stock in relation to extension of CBFM land. This research was carried out in 2009-2010. Estimation of carbon emition is based on analysis of carbon stock changes using RaCSA (Rapid Carbon Stock Appraisal) method that consists of 2 steps: (1) Estimate temporarily land forest cover change through analysis of Landsat satellite from 1995 to 2009, (2) Measuring of carbon stock of land forest cover in various density. Based on remote sensing interpretation Within 14 year period of time, density of land forest cover in Jangkok Watershed has been changing. Forest with high density decrease 43% mean while area for moderate and low density increase by 20% and 17% respectively. Carbon stock for the forest with high density is represented by primary forest about 360 t C/ha, Mahogany forest has 395 t C/ha. Forest with moderate density found in Candlenut forest produces 161 t C/ha and in CBFM about 147 t C/ha with age of tree on average 14 years. Carbon stocking CBFM is varied, the highest was found in area with Candlenut as dominant trees (161 t C/ha), followed area by Mahogany and fruits produced 159 t C/ha, by with Cacao (146 t C/ha), dominant by fruit tree (120 t/ha). Total carbon stock in Forest areas of Jangkok Watershed (12.680 ha) is about 2.02 M t with 25.1% is from CBFM